The Effect of Variations of Drilling Bolt Distances on Bending Strength of Composite Wood Beams - Satia Cahya Noviadi; I Wayan Sugiartha; Jauhar Fajrin (Journal of Science and Science Education, 2022)
Wood products that are currently growing rapidly in many places in the world are laminated blocks (glulam). Laminate beam has many advantages in terms of size, strength and artistic. However, this laminated beam has a few drawbacks in terms of providing tools and materials for some areas. The laminated beam itself uses an adhesive material which is relatively expensive and requires a compression tool in its implementation. Therefore, an alternative is given in the form of composite beams. Composite beams that have developed so far use shear connectors in the form of bolts, nails, and pegs as the connecting tool. Meanwhile, shear connectors using drilling bolts have never been done. Therefore, based on this, it is necessary to research composite wood beams with an alternative, namely using drilling bolts as shear connectors in order to obtain the effect of variations in the distance of drilling bolts on the flexural strength of composite beams. The results of the flexural strength test obtained the strength of the composite beam with shear connectors with the largest distance of 3.125, followed by beams with shear connecting distances of 6.25 cm, 12.5 cm and 25 cm. This shows that the closer the shear connecting distance, the greater the strength obtained, with the percentage increase in variation of 31.5%, 38.737% and 46.072%, respectively.